Qualidade da madeira de clones de Eucalyptus grandis x Eucalyptus urophylla cultivados em cinco regiões do Estado de Minas Gerais para produção de celulose - Barbosa, Thiago Leite (2013)
This study aimed to evaluate the effect of site growth on wood quality at two hybrid clones of Eucalyptus grandis x Eucalyptus urophylla with six years old, planted in five regions of the Minas Gerais state. The wood was derived from clonal plantations of the CENIBRA Company, located in the counties of Belo Oriente, Ferros, Santa Barbara, Itabira and Peçanha. For each clone were selected five trees. Of the trunk of the trees were removed discs in five positions equidistant in the tree height and in the DBH position, to measure the percentage of bark, heartwood and sapwood, and to determine the volume of wood and bark. In laboratory conditions, the wood samples were taken in DBH performed analyzes of anatomical, physical and chemical parameters. The results shown that for the two clones, different sites influenced the growth parameters. To the two clones, the specific gravity varied in the longitudinal direction of the trunk in different patterns according to different regions. The behavior of specific gravity of the wood in the radial direction was similar to the methods of immersion and X-ray densitometry, with increase from pith to bark. The clone B had better indexes of uniformity of density in the radial direction when compared to the clone A, being observed that this index had a better relation with the variables of precipitation and water deficit. To the clone B, the region with the highest average precipitation reflected in a lower frequencies of vessels, however, these had greater diameters, besides the presence of wider fibers, with larger lumen diameters and thicker walls. The fiber length of the clone A was more sensitive to the conditions of precipitation and water deficit. In the chemical analysis, the percentage of extractives, lignin and holocellulose differed significantly for the different places where the two clones were planted, allowing observe the regions with higher precipitation were found higher content of lignin and extractives